Navigating Betrayal and Loyalty: Narrative Construction of Minority Shareholders Regarding Devidend Decisions in Indonesian Family-Controlled Firms - Dewa Ayu Indiana Ida Loemongga Sandopart; Dewa Putu Yohanes Agata L. Sandopart (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study explores the narrative construction employed by minority shareholders as they navigate experiences of betrayal and loyalty concerning dividend policies within Indonesian family-owned enterprises. Utilizing a qualitative approach with an instrumental case study design focused on three family firms listed on the Indonesia Stock Exchange (IDX), the research involved in-depth interviews with 17 minority shareholders (both individual and institutional) whose ownership periods spanned 2 to 20 years. Thematic analysis, following the framework proposed by Braun & Clarke (2006), yielded four principal themes: (1) narratives of exclusion and powerlessness, (2) narratives of ambiguity oscillating between trust and suspicion, (3) narratives of resignation as a coping mechanism, and (4) narratives of conditional loyalty. The findings indicate that minority shareholders construct the meaning of betrayal as a violation of the psychological contract within the dimensions of both distributive and procedural justice. Conversely, loyalty is interpreted as a calculative commitment contingent upon the firm’s performance and the availability of alternative investment opportunities. This research contributes theoretically by enriching agency theory and signaling theory through the integration of a narrative perspective, while also identifying psychological coping mechanisms previously underexplored in the finance literature. Policy implications for capital market regulators and family-controlled companies are discussed.